2016
DOI: 10.1002/2016jb013155
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelasticity of Fe7C3 under inner core conditions

Abstract: It has recently been reported, on the basis of extrapolated experimental data, that the iron carbide, Fe7C3, has shear wave velocities and a Poisson's ratio consistent with the seismological values for the Earth's inner core and thus that Fe7C3 is a strong candidate for the inner core composition. In this study, using ab initio molecular dynamics simulations, we report the thermoelastic properties of Fe7C3 at 350 GPa up to its melting temperature. Due to significant elastic softening prior to melting, the calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 56 publications
(132 reference statements)
6
27
1
Order By: Relevance
“…Furthermore, recent experimental results also suggest that o‐Fe 7 C 3 [ Prescher et al ., ] is a potentially important phase for interpretation of the properties of the Earth's core. However, results obtained from ab initio molecular dynamics simulations claim that the density of Fe 7 C 3 can have a too low density relative to the inner core [ Li et al ., ]. Recent inelastic X‐ray scattering measurements of liquid iron‐carbon alloy show that V P is substantially slower than a phase consisting of pure Fe and Fe 3 C and faster than that of liquid Fe [ Nakajima et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent experimental results also suggest that o‐Fe 7 C 3 [ Prescher et al ., ] is a potentially important phase for interpretation of the properties of the Earth's core. However, results obtained from ab initio molecular dynamics simulations claim that the density of Fe 7 C 3 can have a too low density relative to the inner core [ Li et al ., ]. Recent inelastic X‐ray scattering measurements of liquid iron‐carbon alloy show that V P is substantially slower than a phase consisting of pure Fe and Fe 3 C and faster than that of liquid Fe [ Nakajima et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…However, cosmochemical and iron-silicate melt partitioning studies have suggested the carbon content of the whole core is <0.7-1 wt% (Wood et al, 2013;Zhang and Yin, 2012). An ab initio study suggested the density of Fe 7 C 3 was too low to be a substantial component of the inner core (Li et al, 2016), and, in the analysis of equations of state and seismic observations, Morrison et al (2018) find a carbon content of less than 1 wt%. FeO and iron-rich (Mg,Fe)O also have a low v S compared to that of hcp-Fe, suggesting a large oxygen content could explain the low v S of the inner core.…”
Section: Limits To Extrapolationsmentioning
confidence: 99%
“…The close correspondence of the h-phase elastic properties and those of PREM (preliminary reference Earth model) 5 at 350 GPa and 6500 K was shown with molecular dynamic simulations. 19 However, the obtained density is signicantly lower than that of PREM. With evolutionary crystal structure prediction method, which we also applied here, it was shown that the h-Fe 7 C 3 phase is the most energetically favourable modication in the pressure range of 100-400 GPa at 0 K. 20 Fe 7 N 3 was synthesized in the form of the low-pressure 3and high-pressure b-phases.…”
Section: Introductionmentioning
confidence: 77%